DEVELOPMENT OF SUSTAINABILITY REPORTING TOWARDS COMMON STANDARDS - Djalolitdinovna, Makhliyo Atoeva; Xakimovna, Nigina Fuzaylova (PT. Antis International Publisher, 2024)
Purpose – The purpose of this paper is to to study the current “soup of letters”, that is different standard setters and frameworks on sustainability reporting. Design/methodology/approach – This paper conducts a traditional literature review based on the studies investigating the development of sustainability reporting towards common standards. Findings – Overall, we conclude that current insights of the comment letters on why global sustainability standards are required should be delivered; significant information and analyses on the contribution of setting up the coordinated action and demand-driven consultation for high quality and global sustainability standards should be provided, and academic collaboration relevance to meet the growing demand for sustainability reporting harmonization should be enhanced. Research limitations/implications – Drawing upon literature from different fields enables a deeper understanding of the development of sustainability reportingtowards common standards. Nevertheless, the content analysis of the comment letters are excluded and deserve further attention. Originality/value – This paper discusses the need to have the sustainability reporting by presenting its histroical development towards common standards and deliver current insights on why global sustainability standards are required for high quality sustainability standards to meet the growing demand for global harmonization.